2013
DOI: 10.1074/jbc.m112.439513
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Metabotropic Glutamate Receptor 7 (mGluR7) Internalization and Surface Expression by Ser/Thr Protein Phosphatase 1

Abstract: Background: mGluR7 is a presynaptic autoreceptor in the CNS, which is regulated by receptor phosphorylation. Results: Protein phosphatase 1 (PP1) binds to mGluR7, promotes Ser-862 dephosphorylation, and increases receptor surface expression. Conclusion: PP1 regulates mGluR7 trafficking and function. Significance: Because mGluR7 is associated with memory function and neuropsychiatric disorders, understanding underlying regulatory mechanisms is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…We, therefore, propose that the increased probability of release coupled with the increased PLD activity may contribute to multiple vesicular release that results in the constant PPR (Chamberland et al, 2014; Christie and Jahr, 2006; Conti and Lisman, 2003; Oertner et al, 2002) observed and establishes a new synaptic homeostasis that is unresponsive to the pharmacological treatments. Alternatively, mGluR internalization due to increased probability of release in FPS LTM may contribute to the unresponsiveness (Bhattacharya et al, 2004; Pelkey et al, 2005; Suh et al, 2013). A third possibility is that of a ligand-independent action (Lorez et al, 2003) involving mGluR7.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, propose that the increased probability of release coupled with the increased PLD activity may contribute to multiple vesicular release that results in the constant PPR (Chamberland et al, 2014; Christie and Jahr, 2006; Conti and Lisman, 2003; Oertner et al, 2002) observed and establishes a new synaptic homeostasis that is unresponsive to the pharmacological treatments. Alternatively, mGluR internalization due to increased probability of release in FPS LTM may contribute to the unresponsiveness (Bhattacharya et al, 2004; Pelkey et al, 2005; Suh et al, 2013). A third possibility is that of a ligand-independent action (Lorez et al, 2003) involving mGluR7.…”
Section: Discussionmentioning
confidence: 99%
“…Two events, mGluR7 phosphorylation by PKC and mGluR7 binding to the PDZ domain-containing protein PICK1, lead to increased mGluR7 expression [ 51 ]. mGluR7 expression is also increased by inhibitors of protein phosphatase 1 (PP1), which counteracts the action of PKC on mGluR7 [ 52 ]. Rodent studies suggest that the interaction of mGluR7 and PICK1 is critical to proper neural function, as disruption of the mGluR7a-PICK1 complex is sufficient to induce absence epilepsy-like seizures [ 53 ].…”
Section: Role Of Mglur7 In Synaptic Transmissionmentioning
confidence: 99%
“…As mentioned above, the phosphorylation of mGluR5 by active PKC could also be inhibited by binding with CaM in a Ca 2+ dependent manner. Recent studies suggest that mGluR interacting protein Siah1 [ 29 ], Norbin [ 92 ] and PICK1 [ 151 ] which work as competitive inhibitors of CaM may be potential therapeutic anti-epileptic and/or anti-epileptogenic targets. It is therefore reasonable to believe that targeting on CaM may produce significant antiepileptic and/ or antiepileptogenic effect.…”
Section: Mglur Interacting Proteins As Therapeutic Targets In the Conmentioning
confidence: 99%